An Analytical Model for External Auditor Evaluation of the Internal Audit Function Using Belief Functions - DESAI, VIKRAM; ROBERTS, ROBIN W.; SRIVASTAVA, RAJENDRA (Contemporary Accounting Research, 2010)
The purpose of this paper is to advance research in internal audit (IA) evaluation by developing an IA assessment model that considers interrelationships among specific factors used by external auditors to evaluate the strength of the IA function. The model is based on three factors identified by auditing standards and by prior academic research: Competence, Work Performance, and Objectivity. We develop an analytical expression of the model using the belief function framework in order to overcome limitations of prior research. Our results reveal that modeling the “And” relationship is essential for assessing the strength of the IA function. As far as interrelationships are concerned, the analysis shows that, when the three factors have a strong or a perfect relationship, the strength of the IA function remains high even if there is positive or negative evidence about one of the factors. This result holds as long as there are high levels of belief about the other two factors. Further, we demonstrate how the quality of corporate governance affects the evaluation of the IA function and how a cost–benefit analysis can be applied to this framework to help determine the amount of external audit work needed to comply with standards. Our analysis reveals that the extent of external audit work to be carried out by the external auditor depends on the strength of the IA function and the amount of litigation and regulatory costs likely to be faced by the external auditor.